Clinical Characteristics and Outcome in Dogs with Splenic Marginal Zone Lymphoma. (4th June 2013) - O'Brien, D.; Moore, P.F.; Vernau, W.; Peauroi, J.R.; Rebhun, R.B.; Rodriguez, C.O.; Skorupski, K.A.
<x xml:space="preserve">Abstract</x> Background Splenic marginal zone lymphoma (MZL) is a form of indolent B‐cell lymphoma that is not well characterized in dogs. Hypothesis/Objectives The purpose of this study was to describe clinical characteristics and outcome in dogs with splenic MZL confirmed by histopathology, immunophenotyping, and molecular clonality assessment. We hypothesized that affected dogs would have prolonged survival time with splenectomy alone. Animals Thirty‐four dogs were included. Twenty‐nine dogs were diagnosed after splenectomy, and 5 dogs were diagnosed at necropsy. Methods Pathology records were searched for dogs with histologically confirmed splenic MZL. Clinical and outcome data were retrospectively collected by medical record review, and prognostic factors were evaluated. Histopathology was reviewed by a board‐certified pathologist, and tissue sections were subjected to immunophenotyping and molecular clonality assessment by PCR. Results Immunohistochemistry confirmed a B‐cell phenotype for all dogs. Molecular clonality assessment was performed in 33 of 34 dogs, of which 24 had clonal rearrangement of immunoglobulin (Ig) loci, 3 had pseudoclonal rearrangement, and 6 had polyclonal rearrangement. The overall median survival time (MST) for the 29 dogs that underwent splenectomy was 383 days. The MST for 14 of 29 asymptomatic dogs that underwent splenectomy for MZL was 1, 153 days as compared to 309 days for 15/29 dogs with clinical signs referable to splenic MZL (P = .018). Lymph node involvement, hemoabdomen, anemia, chemotherapy, and concurrent malignancy did not affect survival outcome. Conclusions and Clinical Importance Dogs diagnosed with splenic MZL can have prolonged survival with splenectomy alone, without the use of adjuvant chemotherapy. Asymptomatic dogs may have a better survival outcome.